2017
DOI: 10.5230/jgc.2017.17.e7
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes Associated with Operable Gastric Cancer in a Tertiary Care Indian Hospital

Abstract: PurposeData on operable gastric cancer from India is sparse. The purpose of this study was to investigate the clinical details, histopathological demographics, and 5-year overall survival (OS) and disease free survival (DFS) associated with operable, non-metastatic gastric cancer in a dedicated upper gastrointestinal (GI) surgical unit in India.Materials and MethodsData for patients diagnosed with operable gastric cancer between January 2006 and December 2014 were retrospectively analyzed. Data were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
(32 reference statements)
2
5
0
Order By: Relevance
“…In our study, 153 GC/GOJ patients underwent surgery with an overall resectability rate of 53.6 % (82/153) and curative R0 resection rate of 51.9 (68/74) %. These results are comparable with local study conducted in India and also with western studies [29][30][31] though it is lower than 70-90% curative resection rate reported in Japanese and Australian studies [32,33] In our cohort of patients, resectability of proximal cancers was lower than distal ones.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, 153 GC/GOJ patients underwent surgery with an overall resectability rate of 53.6 % (82/153) and curative R0 resection rate of 51.9 (68/74) %. These results are comparable with local study conducted in India and also with western studies [29][30][31] though it is lower than 70-90% curative resection rate reported in Japanese and Australian studies [32,33] In our cohort of patients, resectability of proximal cancers was lower than distal ones.…”
Section: Discussionsupporting
confidence: 91%
“…35 In our study the 5-year DFS and OS, across all stages, were 36.70% and 55.93%. The 5-year and 3-year DFS and OS are comparable to that reported for open surgery by Franklyn et al 28 Even stage-wise breakup for 5-year values is similar. Compared with the laparoscopic surgery in the Italian study, 35 5-year OS was similar in stage 1; however, for stages 2 and 3 it is much better.…”
Section: Discussionsupporting
confidence: 86%
“…The mean age was 62.4 ± 12.5 years (range 48-87); the average body mass index (BMI) was 24.5 ± 3 kg/m 2 (range [21][22][23][24][25][26][27][28][29][30][31]. Pain in the abdomen (38.5%) and dyspepsia (30.7%) were the most common symptoms (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Similarly in the retrospective study conducted by Franklyn et al, 26% of included patients had a BMI less than 18.5 whereas it was close to 50% in our study. 28 These significant variations in patient characteristics when compared with other tertiary centres reflects the unfavorable socioeconomic status of the majority of patients who are treated in this hospital. 29,30 Numerous studies done on malnourished patients undergoing gastrointestinal surgery and gastric cancer surgery in particular concluded that malnourishment portends a poor postoperative course in terms of minor and major morbidity.…”
Section: Discussionmentioning
confidence: 97%